2020
DOI: 10.3390/ijerph17030839
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Anaplastic Large Cell Lymphoma (pcALCL) in the Elderly and the Importance of Sport Activity Training

Abstract: Primary cutaneous anaplastic large cell lymphoma (pcALCL) is part of a spectrum of cutaneous CD30+ lymphoproliferative disease that also includes lymphomatoid papulosis. It often occurs in elderly patients, presenting at a median age of 60 years, although it may occur at any age. It is a CD30+ T-cell neoplasm composed of large cells with anaplastic, pleomorphic, or immunoblastic morphology, with exclusively cutaneous onset and localization. The clinical course of pcALCL is predominantly indolent. Most elderly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In patients with single lesion, local radiation therapy is the choice with the possible addition of R-CHOP. Like for all lymphomas, before starting each chemotherapy protocol, it is good practice to search for HCVAb, HBsAg, and HBcAb to check for any viral reactivation and prevent it with the indicated prophylaxis (28)(29)(30)(31)(32). Patients with generalized lesions are treated as in nodal DLBCLs.…”
Section: Primary Cutaneous Diffuse Large B-cell Lymphoma Leg Typementioning
confidence: 99%
“…In patients with single lesion, local radiation therapy is the choice with the possible addition of R-CHOP. Like for all lymphomas, before starting each chemotherapy protocol, it is good practice to search for HCVAb, HBsAg, and HBcAb to check for any viral reactivation and prevent it with the indicated prophylaxis (28)(29)(30)(31)(32). Patients with generalized lesions are treated as in nodal DLBCLs.…”
Section: Primary Cutaneous Diffuse Large B-cell Lymphoma Leg Typementioning
confidence: 99%
“…5 These example data, together with the data from few small other studies, suggest that the exposure of patients with cancer to SARS-CoV-2 is very risky, and that every possible precaution must be put in place to prevent this from happening. [6][7][8][9][10][11][12] These considerations also apply to the context of bone marrow transplantation. [13][14][15] We have prepared this review article for all doctors who have not had the opportunity to investigate the different aspects of COVID-19 sufficiently, including young infectious disease specialists, hematologists, and general practitioners, who for more than one reason may meet patients with COVID-19, having to make a first diagnosis and the first decisions about it.…”
mentioning
confidence: 99%
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of cancer patients due to an adequate program of physical activity [23][24][25]34] and impact the cancer survival [7], since it reduces the peak oxygen consumption, improves physical capacity, increases self-esteem, reduces accumulated stress, and promotes relaxation [8,11].…”
Section: Discussionmentioning
confidence: 99%